Therapeutic Effects of an Inhibitor of Thioredoxin Reductase on Liver Fibrosis by Inhibiting the Transforming Growth Factor-β1/Smads Pathway - Jiao, Wenxuan; Bai, Man; Yin, Hanwei; Liu, Jiayi; Sun, Jing; Su, Xiaoxia; Zeng, Huihui; Wen, Jinhua (Frontiers in Molecular Biosciences, 2021)
Liver fibrosis is an important stage in the progression of liver injury into cirrhosis or even liver cancer. Hepatic stellate cells (HSCs) are induced by transforming growth factor-β1 (TGF-β1) to produce α-smooth muscle actin (α-SMA) and collagens in liver fibrosis. Butaselen (BS), which was previously synthesized by our group, is an organic selenium compound that exerts antioxidant and tumor cell apoptosis-promoting effects by inhibiting the thioredoxin (Trx)/ thioredoxin reductase (TrxR) system. The aim of this study was to investigate the potential effects of BS on liver fibrosis and explore the underlying molecular mechanisms of its action. Liver fibrosis models were established using male BALB/c mice through intraperitoneal injection of CCl4. BS was administered orally once daily at a dose of 36, 90, or 180 mg/kg. Silymarin (Si), which is a drug used to patients with nonalcoholic fatty liver disease and nonalcoholic steatohepatitis, was administered at a dose of 30 mg/kg per day as a control. The action mechanisms of BS against liver fibrosis progression were examined in HSCs. The study revealed that the activity and expression levels of TrxR were elevated in mouse liver and serum after CCl4-induced liver fibrosis. Oral administration of BS relieved the pathological state of mice with liver fibrosis, showing significant therapeutic effects against liver fibrosis. Moreover, BS not only induced HSCs apoptosis but also inhibited the production of α-SMA and collagens by HSCs by downregulating TGF-β1 expression and blocking the TGF-β1/Smads pathway. The results of the study indicated that BS inhibited liver fibrosis by regulating the TGF-β1/Smads pathway.